PUBLIC AWARENESS OF WASTE MANAGEMENT IN YOGYAKARTA THROUGH THE FRAMEWORK OF ISLAMIC ECOLOGICAL ETHICS - Permadi, Adi; Djamaluddin Perawironegoro; Afwiyah, Fadhilah; Aprillia Syahputri, Arina; Ardina Fitri Sugianti; Mutiara Wilson Putri (International Journal of Multidisciplinary Reseach, 2025)
Municipal solid waste remains a pressing environmental challenge in the Special Region of Yogyakarta (DIY), characterized by the continuous increase in waste generation, limited waste-management infrastructure, and low levels of public awareness and participation. This study aims to identify and analyze public perceptions and attitudes toward waste management across the five administrative regions of DIY through the distribution of 250 questionnaires administered using a random-sampling technique. The collected data were examined using descriptive statistics, k-means clustering, and heatmap visualization. The findings indicate significant variations in awareness and participation levels based on demographic factors such as age, gender, educational background, occupation, and residential area. The clustering analysis categorized respondents into three groups low awareness (34%), moderate awareness (25%), and high awareness (41%) each requiring different forms of intervention. Beyond the social dimension, the results demonstrate that Islamic ethical principles such as cleanliness as part of faith, the prohibition of environmental destruction (fasād), and the human responsibility as khalifah (stewards of the Earth) serve as an ethical and spiritual foundation that can reinforce community-based waste-management initiatives. Overall, the study concludes that addressing the waste crisis in Yogyakarta requires more than infrastructural solutions; it demands cultural transformation, continuous environmental education, and cross-sector collaboration to build collective ecological awareness and sustainable public engagement.